Evaluation of Cardiac Myosin Binding Protein-C3 (cMyBP-C3) as Potential Risk Factor of Acute Coronary Syndrome in Diabetic Patients - Al-Zuhairi, Wafaa Sh.; Sadeghi, Leila; Hassan, Ekhlas Abdallah (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Recent years, the prevalence of Type 2 Diabetes Mellitus (T2DM) has increased annually. The major complication of T2DM is Cardiovascular Disease (CVD). Cardiovascular disease is the main cause of death in T2DM patients, particularly those with comorbid Acute Coronary Syndrome (ACS). The present study aims to determine the cardiac Myosin Binding Protein-C3 (cMyBP-C3) levels in patients with Type 2 Diabetes Mellitus (T2DM) and to examine the relation of cMyBP-C3 levels with the Acute Coronary Syndrome (ACS). Materials and Methods: Eighty diabetic patients with T2DM who are free from cardiovascular conditions were included in the study, with ages ranging from 35 to 65 years. The T2DM patients were categorized into three subgroups based on their glycemic control, determined by their Hemoglobin A1c (HbA1c) levels. Additionally, forty healthy individuals were included as the control group. The cMyBP-C3 and insulin levels in serum samples were measured using the ELISA Kit. The lipid profile results and fasting serum glucose test were measured using an automated chemical analyzer. The HbA1c levels were determined using the HPLC method. Results: The study showed that the serum concentration of cMYBP-C3 in the group with T2DM was significantly higher in comparison to the healthy subjects (p<0.05). There were significantly substantial association between the levels of cMYBP-C3 and three variables: Malondialdehyde (MDA), insulin, and baseline HbA1c%. There was an excellent area under the curve (AUC=0.963, p=0.0001). Conclusion: That circular cMyBP-C3 may serve as a prognostic indicator for the progression of ACS and declining cardiac function in patients with T2DM. Additionally, it was verified that there was a strong correlation between cMyBP-C3 levels and poorly controlled glycemia.
Keywords: cMyBP-C3; Type 2 diabetes; HbA1c; Acute Coronary Syndrome; Cardiac complications; of diabetes